Status Kerentanan Larva Aedes aegypti Terhadap Temephos Di Wilayah Kerja Pelabuhan KKP Kelas II Tarakan - Irayanti, Irayanti; Martini, Martini; Wurjanto, Arie; Susanto, Henry Setiawan; Firmansyah, Yura Witsqa; Ramadhansyah, Muhammad Fadli (Universitas Nasional Karangturi, 2022)
Various methods of vector eradication have been used to overcome the problem of Indonesian dengue fever with the aim of breaking the chain of dengue transmission, one of which is the use of larvicides to eradicate mosquito larvae. The commonly used larvicide is Abate 1G which contains 1% active substance in the form of temephos, but the use of insecticides continuously and in the long term can reduce the killing power of larvicides and resistance can occur more quickly. The aim of this study was to determine the susceptibility status of Aedes aegypti larvae to temephos. This type of research is experimental with post test only control group design. The population in this study were all larvae survey results of larvae in the buffer area of Tarakan City Harbor which will be used as research objects. The samples of this study were initial III and IV instar Aedes aegypti larvae which were the results of raising the first generation (F1) larvae of the survey results. The results showed 80-98% larval mortality at a concentration of 0.02 mg / l at a concentration of 0.02 mg / l with The 24-hour LC50 value was 0.012 mg / l, while the 24-hour LC99 value ranged from 0.035 mg/l. Larvae in the buffer area of the health port office Tarakan were tolerant of temephos and periodic testing should be carried out and if necessary larvicide rotation to avoid resistance